Vocabulary in autism spectrum disorders. Part 2: Qualitative description – the category of things and events - Hrycyna, Ewa (Logopedia Silesiana, 2022)
This article is the second part of a study concerned with vocabulary in autism spectrum disorders. It presents a qualitative description of vocabulary in people with autism, and more precisely – its content aspect. After a short presentation of theoretical and methodological assumptions, the author proceeds to characterize the categories of things and events and their lexical exponents: nouns and verbs. The analysis of the research material, appropriately selected literature, shows that in the language of people with autism, as in the language of people with typical linguistic development, the categories of things and events are clearly represented. There are analogies, similarities, but also differences within specific semantic subcategories and lexical exponents. The research results are highly varied, and the author tries to explain the reasons for this variation. She also determines how the analysis carried out paves the way for further studies on vocabulary in autism.